Synthesis, structural characterisation and cytotoxicity study of tin(IV) compounds containing ONS Schiff bases - Md Yusof, Enis Nadia (2019)
There is an urgent need for substantial investigation of non-platinum drugs with higher activity and improved selectivity to address the problem associated with the use of platinum-based compounds as therapeutic agents. In light of this, diphenyltin(IV), dimethyltin(IV) and tin(IV) compounds were synthesised from the Schiff bases of three series of dithiocarbazate (S-2-methylbenzyldithiocarbazate (S1), S-4-methylbenzyl dithiocarbazate (S2), S-benzyldithiocarbazate (S3)) and two series of thiosemicarbazides (4-methyl-3-thiosemicarbazide and 4-phenyl-3- thiosemicarbazide) with aldehydes, 2-hydroxy-3-methoxybenzaldehyde (oVa) or 2,3-dihydroxybenzaldehyde (catechol). The tin(IV) compounds formed were found to have a general formula of [R2Sn(ONS)] and [Sn(ONS)2] (where R = Me and Ph). The compounds were fully characterised by physico-chemical and spectroscopic methods. The spectroscopic results supported the coordination geometry in which the Schiff bases behaved as tridentate ONS donor ligands coordinating via azomethine nitrogen, thiolo sulphur and phenoxide oxygen atoms. A total of 11 crystal structures of the expected compounds were solved in this work. In order to verify the experimental data, the compounds were optimised using the density functional theory (DFT) method with the B3LYP hybrid exchange correlation functional with LanL2DZ pseudopotential on tin and 6-311G(d,p) Pople basis set for all other atoms. Diphenyltin(IV) compounds showed the most promising cytotoxicity with IC50 values ranging between 0.016 – 4.40 μM against a panel of twelve cancer cell lines (RT-112, EJ-28 (bladder), HT29 (colon), U87, SJ-G2, SMA (glioblastoma), MCF-7 (breast), A2780 (ovarian), H460 (lung), A431 (skin), Du145 (prostate), BE2-C (neuroblastoma) and MIA (pancreatic)). The three diphenyltin(IV) compounds of the oVa series were able to induce the production of Reactive Oxygen Species (ROS) and acted as a cell apoptosis inducer. Good binding interactions for all the diphenyltin(IV) compound series were observed and supported by molecular docking analysis, where hydrogen, electrostatic and hydrophobic binding interactions were observed. This highlights the important of two phenyl groups coordinated directly to the tin ion to enhance the cytotoxicity by strong π-π stacking interactions to biomacromolecules. Diphenyltin(IV) compounds could bring hope in the field of drug development against various diseases including cancers.